Clinical validation of KIF11 overexpression in colorectal cancer and its potential association with the antitumor effects of nitidine chloride - Hui Li; Rui Lin; Ke-Jun Wu; Jin-Cheng Li; Long Wei; Kai Qin; Li-Min Liu; Xiao-Jue Huang; Liu-Hui Mo; Bin Li; Dong-Ming Li; Zong-Yu Li; et al. (Hereditas, 2026)
Abstract Colorectal cancer (CRC) remains a leading cause of cancer mortality with few effective targeted therapies. Kinesin family member 11 (KIF11), a motor protein essential for mitotic spindle assembly, is frequently overexpressed in multiple cancers. We hypothesized that nitidine chloride (NC), a natural benzophenanthridine alkaloid with documented anti-tumor activity, might suppress CRC by targeting KIF11.Molecular docking predicted a strong interaction between NC and KIF11 (− 9.0 kcal/mol). RNA sequencing, quantitative RT-PCR, and immunohistochemistry confirmed that NC treatment markedly downregulated KIF11 expression. Meta-analysis across public datasets showed consistent KIF11 mRNA overexpression in CRC (standardized mean difference [SMD] = 1.33; AUC = 0.87), while in-house immunohistochemistry on 416 clinical specimens demonstrated even stronger protein-level elevation (AUC = 0.99) that correlated with larger tumor size and deeper invasion. Single-cell RNA sequencing and spatial transcriptomics further revealed that KIF11 is preferentially expressed in proliferative malignant epithelial cells. Through CRISPR-based knockout screening and lentiviral silencing, KIF11 depletion impaired the growth or viability of the examined CRC cell models. Public ChIP-seq data suggested RAD21 occupancy near the KIF11 regulatory region, whereas reciprocal co-immunoprecipitation supported an association between the RAD21 and KIF11 proteins. Among genes co-expressed with KIF11,a pronounced enrichment was observed in pathways governing cell-cycle progression. Following KIF11 knockdown, transcriptomic profiling showed reduced expression across cell-cycle, DNA-replication, and chromatin-cohesion programs, alongside a reciprocal increase in amino-acid metabolism and stress-response genes. At the functional level, KIF11 depletion suppressed cell proliferation and induced G2/M-phase arrest. Taken together, these in vitro and limited xenograft data indicate that NC restrains CRC growth chiefly through the RAD21–KIF11 axis; KIF11 represents a promising preclinical target, though comprehensive systematic in vivo pharmacodynamic and translational animal validation remains absent in the current study and requires further independent investigation.